PENGARUH MOTIVASI KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN CV SURYA UNGGUL SENTOSA (SUS) KOTA BIMA (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the effect of work motivation and work stress on employee productivity at CV Surya Superior Sentosa (SUS) Bima City. This type of research is associative with the research tool is a questionnaire. The population in this study were 40 employees and the sampling technique using a saturated sample was all employees at CV. Surya Abadi Sentosa excelled as many as 40 people with the sample. Data collection techniques in this study using observation, questionnaires, documentation and literature study. The analysis technique used in this research is validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination, t test and f test. From the results of the analysis, it can be concluded that there is a partially significant effect of motivation on employee work productivity, there is a partially significant influence of organizational culture on employee performance, there is a simultaneous influence of motivation and work stress on employee productivity.